IMPLEMENTATION OF THE CONCEPT OF "FAMILY" IN THE MODERN SOCIETY - Rozentale, Lidija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
There is a continuous debate in the public space on the need for a legal framework for the partnership institute to ensure equal legal security for the family, regardless of the existence or non-existence of the legal fact of its foundation. The fundamental aspects of the debate include the insufficient regulatory framework and vulnerability of partners before the law, divergent national views on partnerships as a union between opposite-sex partners, religious beliefs condemning non-marital relationships, including the existing property issues in the context of partnerships. According to the Author of the Paper, the existing partnerships in Latvia are discriminated in favour for the marriage due to the moral views and legal aspects, as the individual living in the partnership is restricted in terms of access to information and is vulnerable in terms of property rights. For example, when an individual lives in the partnership, he or she is denied the right to be informed about the health status of the other partner and the existing liabilities in credit institutions. In cohabitation, the individual is not recognised as a member of the family of the tenant for the purpose of the Law on Residential Tenancy and the potential consequences of the partnership may be the denied right to inheritance or tenancy.Main methods used: sociological method for analysing the compliance of laws and regulations with public interests and aims.